Pembinaan dan Pendampingan Masyarakat dalam Rangka Mewujudkan Pencapaian Ketahanan Pangan Nasional (Food Estate) Provinsi Sulawesi Barat - Jasmin Ambas; Syamsuddin Hasan; Andi Atssam Mappanyukki; Andi Ulfiana Fitri; Meliana Handayani; Syamsu Arif; Amriana Hafiza; Fatmawati Chaerunnisa; Anas Qurniawan (jurnal ABDIMAS Indonesia, 2023)
The high number of stunting cases in Indonesia is in the spotlight of WHO, so that stunting cases are given serious attention by the government by making preventing and reducing the number of stunting cases a national program through the collaboration of several ministries. Based on this, the government launched food estates as a national strategic program for 2020-2024. It is hoped that this program will be a solution to overcome the high number of stunting cases while reducing the number of stunting cases that have been found. The food estate program approach, which is expected to have an impact on reducing and preventing stunting cases, uses the "zero waste furming system" method, namely the use of corn and oil palm plantations that have developed so far as beef cattle farms where corn and plantation waste are processed into animal feed. and livestock manure and urine are processed into biogas and organic fertilizer which are really needed by corn and oil palm plants. The intervention program to reduce and prevent stunting rates in Central Mamuju Regency is carried out comprehensively through a food security program (food estate) and providing additional nutrition and other nutritional needs, especially for community groups who are vulnerable to nutritional and protein deficiencies.